Composition, diversity and structure of tree communities along an altitudinal gradient of subtropical forests of mountain (foothills of Zapla, Jujuy, Argentina) - Erica Cuyckens, Griet An; Ricardo Malizia, Lucio; Blundo, Cecilia (Instituto de Ecología, A.C., 2016)
Altitudinal gradients are associated with climatic gradients that promote species diversity. This study describes the composition, diversity and structure of trees along an altitudinal gradient in subtropical mountain forests (Yungas) in Serranías de Zapla, Jujuy province, Argentina. Three 1-ha plots at 1150 m, 1600 m and 2050 m above sea level were established. Each plot was subdivided into 25 subplots, where all trees ≥10 cm of diameter at breast height (dbh) were measured and identified as for species; number of species, diversity, and density of individuals, basal area, and dominance of individuals per species among elevations were compared. The effect of distance on species turnover was analyzed, and the relations between abundance of individuals per species and frequency of species occurrence was evaluated. We sampled 1375 individuals belonging to 46 species. A significant turnover in species composition along the gradient was found: only three species were present at all elevations, and most species (29) were found at a single altitude. Species richness and diversity decreased with altitude, density of individuals showed no clear pattern, basal area peaked at 1600 m, and dominance was more pronounced at higher altitudes. Low Montane Forest (1150 m) and High Montane Forest (2050 m) were clearly different in terms of species composition. Species similarity was negatively associated with distance within each altitudinal level. Abundance of individuals per species was positively associated with frequency of species occurrence. This study confirms the community organization of tree species in altitudinal ecological levels determined by environmental variables in Yungas forests, and emphasizes the importance of local factors in determining the diversity, composition and structure of these communities.